A case study on the feasibility and utility of continuous glucose monitors in elite football - Harries, S.; Clayton, D.; Johnson, M.; Burberry, R.; Varley, I. (International Journal of Sport Nutrition and Exercise Metabolism, 2025)
Physiological performance may be limited by reduced systemic glucose availability, reducing the supply of glucose to the working muscles. Continuous glucose monitors (CGM) provide repeated measures every 1-15 minutes of interstitial glucose, potentially providing a practical way of assessing glucose concentrations during sporting activity. However, empirical research has predominantly focused on endurance-based sports and `real-time` glucose responses during a professional competitive football match remain unknown. This study aimed to evaluate the feasibility and utility of CGM in elite football and the applications for practice. Eight elite, male outfield footballers competing in the third tier of English football during the 23/24 season participated in the study. Participants completed a 14-day food diary control period, followed by a 28-day observation period wearing a CGM device. Throughout the study, daily dietary reporting comprised a photographed "snap and send" food diary. The CGM device was placed on the back of the upper arm. Six matches and sixteen training sessions took place during the observation period. CGM devices remained in situ for 98% of training sessions and matches. Average glucose concentrations were 6.5 ± 1.2 mmol/L during training sessions, 7.5 ± 2.1 mmol/L during match play, and 5.4 ± 0.3 mmol/L overnight. There were no differences in glucose concentrations in response to match-play (P = 0.060) or training (P = 0.510) compared to overnight fasted glucose concentrations. There was also no difference between training and match-play glucose concentrations (P = 0.788). Glucose concentrations were highly individualised, with one player displaying minimal change throughout match play (-0.2 mmol/L) whereas another experienced increases of 5.8 mmol/L. Glucose concentrations also appeared to be influenced by non-nutritional interventions: for example, participants (n=3) who used nicotine pouches displayed an acute transient increase in blood glucose in the 10-60 minutes after administration. To conclude, this study suggests that CGM use in elite football is feasible and could be useful in assessing individuality in glucose response to training and match-play.